Svātantryavīra Bê. Vināyaka Dāmodara Sāvarakara yāñcẽ jīvana-caritra - Bhope, Raghunātha Gaṇeśa (SAMP early 20th-century Indian books project, 1938)
Life of Vinayak Damodar Savarkar, 1883-1966, Indian freedom fighter.